2011
DOI: 10.2967/jnumed.110.078360
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Hepatic Function During Liver Regeneration in a Standardized Rat Model

Abstract: Reliable assessment of hepatic function during liver regeneration is crucial after liver surgery or liver transplantation. 99m Tcgalactosyl human serum albumin ( 99m Tc-GSA) scintigraphy, 99m Tc-mebrofenin hepatobiliary scintigraphy (HBS), the indocyanine green (ICG) clearance test, and the galactose elimination capacity (GEC) are common quantitative liver function tests. However, to our knowledge, comparative analysis between these tests has never been performed during liver regeneration. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 34 publications
2
39
0
1
Order By: Relevance
“…Several studies have reported a more advanced increase in liver function versus increase in volume [68,69,70], although the available studies do not deliver clear evidence for this statement due to methodological and analytical errors, leaving this question to be answered in the future. Moreover, the 99m Tc-GSA uptake may underestimate hepatic regeneration in the later stages of liver regeneration, as shown by de Graaf et al [71] in a rat model.…”
Section: Scintigraphic Liver Function Testsmentioning
confidence: 86%
“…Several studies have reported a more advanced increase in liver function versus increase in volume [68,69,70], although the available studies do not deliver clear evidence for this statement due to methodological and analytical errors, leaving this question to be answered in the future. Moreover, the 99m Tc-GSA uptake may underestimate hepatic regeneration in the later stages of liver regeneration, as shown by de Graaf et al [71] in a rat model.…”
Section: Scintigraphic Liver Function Testsmentioning
confidence: 86%
“…We recently compared the ICG clearance test with 99m Tc-mebrofenin HBS in rats after ischemia-reperfusion injury combined with a partial hepatectomy(7) and during liver regeneration after major hepatectomy (40). In both models a differential decrease in OATP isoforms was observed, contributing to the difference in hepatic uptake between ICG and 99m Tc-mebrofenin after ischemia-reperfusion injury and during regeneration.…”
Section: Inhibition Of Oatp-mediated Transport By Icg Earlier Studiesmentioning
confidence: 99%
“…Therefore, it follows that the smaller the graft, the greater is the proportion of hepatocytes entering the replicative process to form these islands, decreasing the amount of functional liver tissue available even as gross mass is restored (44). This helps explain why multiple studies, including our own, have reported that functional regeneration does not correlate with volumetric regeneration during the early stages of liver regrowth (4,5,(51)(52)(53)(54) and that strategies that decelerate regeneration can actually lead to better preservation of normal hepatic microarchitecture and improved survival during the regenerative process (43).…”
Section: Discussionmentioning
confidence: 81%